(A study on Packaging of Molded Palm sugar) - -, Sardjono; Basrah Enie, A; Sukardi, Oyok (Warta Industri Hasil Pertanian, 1987)
A Study on the packaging of molded Arenga palm Sugar had Been carried out. The packaging materials used were plastics film, aluminium foil, and paper coated with plastic. The moisture content, reducing sugar and sugar colour were observed during 12 weeks of storage. The result showed that the packaging materials used did not significantly affect the moisture content, reducing sugar, and colour during 12 weeks storage. After 12 weeks, the moisture content were 7.01-8.89 percent, Reducing sugar 1.61-1.94 percent and colour 92.04-96.43 I.U